Students' perceptions of Plickers and crossword puzzles in undergraduate studies. Issue 2 (13th February 2020) - Mshayisa, Vusi Vincent
Abstract: In higher education, there are calls to incorporate active learning experiences that place the student at the center of learning, rather than encouraging students to be passive listeners. For students to have a deeper and more meaningful learning experience, educators can use an active learning approach. This approach attempts to engage students at higher levels of thinking so that they are more interested in, better engaged with, and understand the course material better. The aim of this study was to investigate students' perceptions of Plickers and crossword puzzles as low‐cost pedagogical tools to foster active learning in an undergraduate course in food science and technology. A mixed‐method survey consisting of a 5‐point Likert scale and open‐ended qualitative questions was administered via Blackboard to elicit student responses. A total of 121 students were enrolled for the course and 70.2% ( n  = 85) completed the survey. Plickers were found to be easy to use (mean = 4.66), provided opportunities to answer to formative questions anonymously (mean = 4.60), and helped increase participation in class (mean 4.05). The majority of students felt that crossword puzzles required them to think critically (mean = 4.53) and provided them with the opportunity to assess how well they understood the course content (mean = 4.45). Moreover, a statistically positive relationship was found between student collaborative learning and crossword puzzle implementation scores ( r  = .506, p  < .01). The findings demonstrated that when implemented effectively, Plickers and crossword puzzles contributed to greater enhanced student engagement. These pedagogical tools can be applied as formative assessment instruments and offer a low‐cost alternative to the limitations encapsulated by didactic pedagogy.